Outcomes of patients with perforated colon cancer: A systematic review. Issue 1 (January 2023) - Zamaray, B.; van Velzen, R.A.; Snaebjornsson, P.; Consten, E.C.J.; Tanis, P.J.; van Westreenen, H.L.
Abstract: Introduction: Perforated colon cancer (PCC) is a distinct clinical entity with implications for treatment and prognosis, however data on PCC seems scarce. The aim of this systematic review is to provide a comprehensive overview of the recent literature on clinical outcomes of PCC. Materials and methods: A systematic literature search of MEDLINE (PubMed), Embase, Cochrane library and Google scholar was performed. Studies describing intentionally curative treatment for patients with PCC since 2010 were included. The main outcome measures consisted of short-term surgical complications and long-term oncological outcomes. Results: Eleven retrospective cohort studies were included, comprising a total of 2696 PCC patients. In these studies, various entities of PCC were defined. Comparative studies showed that PCC patients as compared to non-PCC patients have an increased risk of 30-day mortality (8–33% vs 3–5%), increased post-operative complications (33–56% vs 22–28%), worse overall survival (36–40% vs 48–65%) and worse disease-free survival (34–43% vs 50–73%). Two studies distinguished free-perforations from contained perforations, revealing that free-perforation is associated with significantly higher 30-day mortality (19–26% vs 0–10%), lower overall survival (24–28% vs 42–64%) and lower disease-free survival (15% vs 53%) as compared to contained perforations. Conclusion: Data on PCC is scarce, with various PCC entities defined in the studies included. Heterogeneity of the study population, definition of PCC and outcome measures made pooling of the data impossible. In general, perforation, particularly free perforation, seems to be associated with a substantial negative effect on outcomes in colon cancer patients undergoing surgery. Better definition and description of the types of perforation in future studies is essential, as outcomes seem to differ between types of PCC and might require different treatment strategies.